(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Mint distillation, a common method for extracting essential oils from mint, traditionally relies on steam distillation, which is both energy-intensive and water-consuming. To address these sustainability concerns, we propose an innovative approach to enhance the solar thermal efficiency of mint oil distillation systems. Our method involves using selective coatings on the absorber plates. These coatings are designed to absorb solar radiation efficiently and convert it into heat while minimizing thermal losses. The absorber plate, integrated with a copper tube network, is coated with a selective material that has shown a temperature increase of 15-20°C compared to conventional black coatings. This improvement in temperature not only boosts the yield and quality of mint oil but also reduces water usage and environmental impact. Selective coatings manipulate the absorption and emissivity properties of the absorber plate, tailoring them specifically to the distillation process.